2018
DOI: 10.1016/j.repc.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Massive organ embolization from primary aortic thrombosis

Abstract: A 49-year-old woman was hospitalized for acute left foot arterial ischemia. Arterial Doppler revealed occlusion of the dorsalis pedis and posterior tibial arteries. A computed tomography angiography performed to assess abdominal pain showed hepatic, splenic, renal and pancreatic infarctions. A splenic artery embolism and a small aortic wall thrombus at the celiac trunk were identified. No radiological signs of aortic atherosclerosis were found. No predisposing conditions for secondary aortic thrombosis or intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
2
3
1
Order By: Relevance
“…PAO clinical presentation is sudden and depends on the aortic occlusion level and thrombus localization. In our study, similarly to others [3,26,28,29], the majority of our patients (81.8%) were admitted to the Emergency Department with clinical signs and symptoms of acute onset of lower limb functional impotence, pain, hypothermia and ischemia. In these patients, the diagnosis can be suspected when the acute onset of lower limb symptoms is associated with the absence of femoral pulses, but in cases of paraplegia or sudden lower limb impotence, a correct differential diagnosis with neurological disease can be more complex and may delay the diagnosis.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…PAO clinical presentation is sudden and depends on the aortic occlusion level and thrombus localization. In our study, similarly to others [3,26,28,29], the majority of our patients (81.8%) were admitted to the Emergency Department with clinical signs and symptoms of acute onset of lower limb functional impotence, pain, hypothermia and ischemia. In these patients, the diagnosis can be suspected when the acute onset of lower limb symptoms is associated with the absence of femoral pulses, but in cases of paraplegia or sudden lower limb impotence, a correct differential diagnosis with neurological disease can be more complex and may delay the diagnosis.…”
Section: Discussionsupporting
confidence: 76%
“…Although any significant difference between male and female genders has never been reported in the literature [3], in our study, we found that there was a mild prevalence in males (male/female ratio: 2.66/1). The mean age of our population was 65.27 years old, slightly older than what has previously been reported (<50 years old patients mean age) [27][28][29].…”
Section: Discussioncontrasting
confidence: 58%
“…The surgical approach was only indicated for patients who do not respond to conservative treatment. 19 - 21 , 23 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…Regarding the choice of anticoagulation drug, most studies used unfractionated heparin (UFH) for a short period of time and then switched to warfarin, 20 , 22 , 24 , 25 targeting an international normalized ratio (INR) between 2 and 3 20 , 25 or 2.5 and 3.5. 24 The duration of treatment remains uncertain and should be individualized, ranging from 4 months to lifelong for patients with a history of hypercoagulable state. 19 , 20 One patient was maintained on 100 mg aspirin alone after a warfarin regimen.…”
Section: Resultsmentioning
confidence: 99%
“…But the risk of recurrent embolization was higher with the use of VKA; hence, many authors adopted an aggressive surgical or endovascular approach or combined hybrid approach in some of the cases where there was extensive thrombosis and risk of recurrent embolization was higher. 8 …”
Section: Short Communicationmentioning
confidence: 99%